O método psico-histórico-espiritual : uma proposta de acompanhamento espiritual a partir dos exercícios espirituais de Inácio de Loyola - Knapp, Jorge álvaro (2007)
The Psycho-historical-Spiritual method is a proposal of spiritual direction from the perspective Ignatius of Loyola s Spiritual Exercises. Therefore, the first part of this thesis takes on the history of Ignatius of Loyola's experience. It explains his biography, his religious profile, the genesis of the Spiritual Exercises, its systematization and the dynamics of its method. Then, it presents some elements of the Ignatian spirituality, fruits of the Spiritual Exercises method. The Thesis second part presents the report of some people who discovered the Spiritual Exercises and they were directed through this experience in different forms, underlining the high points, their difficulties, and the fruits of this journey. In the third and last part I present Carlos Rafael Cabarrús psycho-historical-spiritual method as an actualization of the spiritual direction during the Spiritual Exercises in current context taking into consideration the whole person, i.e., the spiritual, psychological, historical dimensions fostering an integral and qualified guidance within the complexity of the current historical reality.